Low doses of cholera toxin and its mediator cAMP induce CTLA-2 secretion by dendritic cells to enhance regulatory T cell conversion - Silva-Vilches, Cinthia; Pletinckx, Katrien; Lohnert, Miriam; Pavlovic, Vladimir; Ashour, Diyaaeldin; John, Vini; Vendelova, Emilia; Kneitz, Susanne; Zhou, Jie; Chen, Rena; Reinheckel, Thomas; Müller, Thomas; et al. (PLOS ONE, 2017)
Immature or semi-mature dendritic cells (DCs) represent tolerogenic maturation stages that can convert naive T cells into Foxp3+ induced regulatory T cells (iTreg). Here we found that murine bone marrow-derived DCs (BM-DCs) treated with cholera toxin (CT) matured by up-regulating MHC-II and costimulatory molecules using either high or low doses of CT (CThi, CTlo) or with cAMP, a known mediator CT signals. However, all three conditions also induced mRNA of both isoforms of the tolerogenic molecule cytotoxic T lymphocyte antigen 2 (CTLA-2α and CTLA-2β). Only DCs matured under CThi conditions secreted IL-1β, IL-6 and IL-23 leading to the instruction of Th17 cell polarization. In contrast, CTlo- or cAMP-DCs resembled semi-mature DCs and enhanced TGF-β-dependent Foxp3+ iTreg conversion. iTreg conversion could be reduced using siRNA blocking of CTLA-2 and reversely, addition of recombinant CTLA-2α increased iTreg conversion in vitro. Injection of CTlo- or cAMP-DCs exerted MOG peptide-specific protective effects in experimental autoimmune encephalomyelitis (EAE) by inducing Foxp3+ Tregs and reducing Th17 responses. Together, we identified CTLA-2 production by DCs as a novel tolerogenic mediator of TGF-β-mediated iTreg induction in vitro and in vivo. The CT-induced and cAMP-mediated up-regulation of CTLA-2 also may point to a novel immune evasion mechanism of Vibrio cholerae.
Gesehen am 19.08.2019